Conductance in a bis-terpyridine based single molecular breadboard circuit. Issue 2 (11th November 2016) - Seth, Charu; Kaliginedi, Veerabhadrarao; Suravarapu, Sankarrao; Reber, David; Hong, Wenjing; Wandlowski, Thomas; Lafolet, Frédéric; Broekmann, Peter; Royal, Guy; Venkatramani, Ravindra
Abstract : We study conductance in a molecular breadboard junction accommodating up to 61 circuits and demonstrate switching between 4 conductance states. Abstract : Controlling charge flow in single molecule circuits with multiple electrical contacts and conductance pathways is a much sought after goal in molecular electronics. In this joint experimental and theoretical study, we advance the possibility of creating single molecule breadboard circuits through an analysis of the conductance of a bis-terpyridine based molecule (TP1 ). TheTP1 molecule can adopt multiple conformations through relative rotations of 7 aromatic rings and can attach to electrodes in 61 possible single and multi-terminal configurations through 6 pyridyl groups. Despite this complexity, we show that it is possible to extract well defined conductance features for theTP1 breadboard and assign them rigorously to the underlying constituent circuits. Mechanically controllable break-junction (MCBJ) experiments on theTP1 molecular breadboard show an unprecedented 4 conductance states spanning a range 10 −2 G 0 to 10 −7 G 0 . Quantitative theoretical examination of the conductance ofTP1 reveals that combinations of 5 types of single terminal 2–5 ring subcircuits are accessed as a function of electrode separation to produce the distinct conductance steps observed in the MCBJ experiments. We estimate the absolute conductance for each single terminal subcircuit and its percentage contribution to the 4 experimentally observed conductance states. We also provide a detailed analysis of the role of quantum interference and thermal fluctuations in modulating conductance within the subcircuits of theTP1 molecular breadboard. Finally, we discuss the possible development of molecular circuit theory and experimental advances necessary for mapping conductance through complex single molecular breadboard circuits in terms of their constituent subcircuits.